Cutaneous Plasmacytoma: Metastasis of Multiple Myeloma at the Fracture Site - Yoo, Jisook (Ann Dermatol, 2017)
Multiple myeloma (MM) can be defined as a malignancy with monoclonal plasma cell proliferation. A 66-year-old man presented with pruritic erythematous to purplish plaque grouped nodule with black pigmentations and purpura on the right forearm. The patient was diagnosed with MM about five years prior to the visit at our hospital. Erythematous plaque on his right arm grew rapidly in size over one month and appeared about seven months after the fracture surgery. Skin biopsy showed multiple plasma cell infiltration with monoclonality for lambda light chain, which was consistent with cutaneous plasmacytoma. The patient refused to be treated and died two months later. We herein report an interesting case of cutaneous plasmacytoma at the surgical site of fracture repair.